Pengelolaan Persediaan Bahan Baku pada Telur Asin Besek Pring Kang Noer Bukit Kencana Jaya Semarang - Surjawati, Surjawati; Widowati, Amerti Irvin; Wahdi, Nirsetyo (Fokus ABDIMAS, 2024)
Besek Pring Kang Noer Salted Eggs, is the name of a salted egg and smoked egg making business located at Jalan Bukit Cemara Indah XI C2 No 53 Bukit Kencana Jaya Semarang housing estate. This business has been started since 2012, and its turnover is now an average of 2000 to 3000 eggs every month. This business not only sells cooked salted eggs but also sells raw duck eggs, raw salted eggs, and smoked salted eggs with prices ranging from Rp 2,800 to Rp 4,000 per grain. This business has also tried to make simple business financial records but has not made more detailed financial reports. The problem that often occurs in this salted egg business is the problem of raw material availability in the form of raw duck eggs.duck eggs purchased from breeders. During the weather change season, sometimes ducks do not want to lay eggs so that the supply of raw eggs becomes small, even though at that time consumer demand is high. On the other hand, when consumer demand is down, the supply of these eggs is high. The FE USM Community Service Team (PKM) shared about the problems in this salted telr making business. We titled this activity "Inventory Management of Salted Egg Raw Materials at Besek Pring Kang Noer"..